How to avoid destroying your employees and organisations due to burnouts, braindrain and fading performance? Stop double bind-communication in your organisation! - Angelika Kutz (Journal of Organization Design, 2017)
Absenteeism due to "burnout", depression or other psychological diagnoses, is increasing alarmingly in modern work life. This point of view describes presumed connections between the double bind-communication pattern in organisations and its detrimental consequences for both the employees of a double bind-organisation and such double bind-organisations themselves. The employees fall psychologically, psychosomatically or physically ill due to a double bind caused self-esteem-destruction-machinery, the organisations run the risk of self-destruction because the double bind-communication impedes the organisation from learning, evolving and developing new solutions and from adapting to the challenges of changing environments in time.
Keywords: 650; Double bind; Double bind-organisations; Traumatising toxic communication; Paradox messages; Absenteeism due to psychological illness; Burnout; Depression